1988
DOI: 10.1523/jneurosci.08-09-03144.1988
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of the amygdala from visual association cortex impairs visual reward-association learning in monkeys

Abstract: Cynomolgus monkeys (Macaca fascicularis) were trained in a task that assessed their ability to associate visual stimuli with food reward. Acquisition of stimulus-reward associations was measured under 2 conditions, a 2-stimuli acquisition condition and a 1-stimulus acquisition condition. On each trial in the 2-stimuli condition, the positive (correct) and negative (incorrect) stimuli were presented side by side and the animal chose one by touching it; if the choice was correct, a food reward was dispensed. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 7 publications
10
53
1
1
Order By: Relevance
“…A positron emission tomography study attempting to separate decontextualized human motions (point-light displays depicting a hand bringing a cup to one's mouth) from what can be seen as a more naturalistic human motion (a person dancing) showed that the perception of the latter also implicated limbic structures such as the amygdala (Bonda et al 1996). This finding is consistent with a perceptionfor-action system that not only perceives to act, but one that is embedded in an approach/withdrawal, affectivebased context (Gaffan et al 1988).…”
Section: Contextual Elements In the Emergence Of Mental Representationssupporting
confidence: 52%
“…A positron emission tomography study attempting to separate decontextualized human motions (point-light displays depicting a hand bringing a cup to one's mouth) from what can be seen as a more naturalistic human motion (a person dancing) showed that the perception of the latter also implicated limbic structures such as the amygdala (Bonda et al 1996). This finding is consistent with a perceptionfor-action system that not only perceives to act, but one that is embedded in an approach/withdrawal, affectivebased context (Gaffan et al 1988).…”
Section: Contextual Elements In the Emergence Of Mental Representationssupporting
confidence: 52%
“…Specifically, a unilateral lidocaine-induced lesion of the origin of parallel efferent pathways in one hemisphere was used in combination with a contralateral lidocaine-induced lesion in one of the target areas of the efferent projection in the other hemisphere. This procedure has proven to be particularly useful in defining the route of serial information transfer between different brain regions in both rats (Everitt et al, 1991) and primates (Gaffan and Harris, 1987;Gaffan et al, 1988Gaffan et al, , 1989. Two patterns of bilateral inactivation were used in the following experiments: unilateral reversible lesions of the vSub in combination with a contralateral lesion of either (1) the PL region of the PFC or (2) the N.Acc.…”
Section: Abstract: Ventral Ca1/subiculum; Prelimbic Cortex; Nucleus mentioning
confidence: 99%
“…The amygdala has been strongly implicated in both visual learning and memory, the formation of object-reward associations, as well as in affective behavior (e.g. Spiegler & Mishkin, 1981;Mishkin, 1982;Saunders et al, 1984;Gaffan & Harrison, 1987;Gaffan et al, 1988;Gaffan & Murray, 1990), functions for which object identity but not visuospatial information is required.…”
Section: Amygdalamentioning
confidence: 99%